2015
DOI: 10.17537/2015.10.15
|View full text |Cite
|
Sign up to set email alerts
|

Ground Vegetation Modeling through Functional Species Groups and Patches in the Forest Floor

Abstract: Аннотация. Разработана система функциональных групп видов растений, предназначенная для моделирования динамики лесного напочвенного покрова. На основе количественного анализа сведений из литературных источников и авторских данных, дана характеристика биомассы различных типов микрогруппировок, выделяемых в лесном напочвенном покрове по доминирующей функциональной группе видов. Путем обработки информации, объединенной в оригинальные базы данных «Биомасса» и «Элементы», показано, что варьирование значений надземн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…It was also found that the contents of Al, Fe, Mn, and Mg were relatively equal in tall-herb fir-spruce forest plants of the boreal tall-herb, boreal low-herb, and nemoral tall-herb groups. Similar results were obtained for the same functional groups of species in the northern-boreal and middle-boreal European Russia, where boreal tall and low herbs were discovered to be the closest groups in terms of their chemical composition (Khanina et al, 2015). It is indicated that these functional groups differ significantly in their characters from dark-conifer and light-conifer boreal dwarf-shrubs, the oligotrophic group species, and mosses which generally all have similar characters.…”
Section: Discussionsupporting
confidence: 74%
“…It was also found that the contents of Al, Fe, Mn, and Mg were relatively equal in tall-herb fir-spruce forest plants of the boreal tall-herb, boreal low-herb, and nemoral tall-herb groups. Similar results were obtained for the same functional groups of species in the northern-boreal and middle-boreal European Russia, where boreal tall and low herbs were discovered to be the closest groups in terms of their chemical composition (Khanina et al, 2015). It is indicated that these functional groups differ significantly in their characters from dark-conifer and light-conifer boreal dwarf-shrubs, the oligotrophic group species, and mosses which generally all have similar characters.…”
Section: Discussionsupporting
confidence: 74%